Ruthenium-106 brachytherapy for thick uveal melanoma: reappraisal of apex and base dose radiation and dose rate - Naseripour, Masood; Jaberi, Ramin; Sedaghat, Ahad; Azma, Zohreh; Nojomi, Marzieh; Falavarjani, Khalil Ghasemi; Nazari, Hossein (Journal of Contemporary Brachytherapy, 2016)
Purpose: To evaluate the outcomes of ruthenium-106 ( 106 Ru) brachytherapy in terms of radiation parameters in patients with thick uveal melanomas. Material and methods: Medical records of 51 patients with thick (thickness ≥ 7 mm and < 11 mm) uveal melanoma treated with 106 Ru brachytherapy during a ten-year period were reviewed. Radiation parameters, tumor regression, best corrected visual acuity (BCVA), and treatment-related complications were assessed. Results: Fifty one eyes of 51 consecutive patients including 25 men and 26 women with a mean age of 50.5 ± 15.2 years were enrolled. Patients were followed for 36.1 ± 26.5 months (mean ± SD). Mean radiation dose to tumor apex and to sclera were 71 (± 19.2) Gy and 1269 (± 168.2) Gy. Radiation dose rates to tumor apex and to sclera were 0.37 (± 0.14) Gy/h and 6.44 (± 1.50) Gy/h. Globe preservation was achieved in 82.4%. Preoperative mean tumor thickness of 8.1 (± 0.9) mm decreased to 4.5 (± 1.6) mm, 3.4 (± 1.4) mm, and 3.0 (± 1.46) mm at 12, 24, and 48 months after brachytherapy (p = 0.03). Four eyes that did not show regression after 6 months of brachytherapy were enucleated. Secondary enucleation was performed in 5 eyes because of tumor recurrence or neovascular glaucoma. Tumor recurrence was evident in 6 (11.8%) patients. Mean Log MAR (magnification requirement) visual acuity declined from 0.75 (± 0.63) to 0.94 (± 0.5) (p = 0.04). Best corrected visual acuity of 20/200 or worse was recorded in 37% of the patients at the time of diagnosis and 61.7% of the patients at last exam (p = 0.04). Non-proliferative and proliferative radiation-induced retinopathy was observed in 20 and 7 eyes. Conclusions : Thick uveal melanomas are amenable to 106 Ru brachytherapy with less than recommended apex radiation dose and dose rates.